Serial 18F-choline-PET imaging in patients receiving enzalutamide for metastatic castration-resistant prostate cancer: response assessment and imaging biomarkers. (February 2016) - Maines, Francesca; Caffo, Orazio; Donner, Davide; Sperduti, Isabella; Bria, Emilio; Veccia, Antonello; Chierichetti, Franca; Tortora, Giampaolo; Galligioni, Enzo
Aim: High rate of non-target lesions in metastatic castration-resistant prostate cancer usually limits applicability of Response Evaluation Criteria in Solid Tumors (RECIST) criteria, and this has led to a growing interest in using PET/computed tomography (CT). We prospectively investigated the role of 18 F-choline (FCH)-PET/CT in patients receiving enzalutamide after docetaxel.Patients & methods: 30 patients were monitored by means of FCH-PET/CT before and during the treatment. A Cox proportional hazards regression model was used to assess the associations between metabolic parameters and clinical outcomes.Results: Univariate analysis showed no significant correlation between biochemical and FCH-PET responses. Multivariate analysis showed that only baseline maximum standardized uptake value (SUVmax ) significantly correlated with biochemical progression-free survival, radiological progression-free survival and overall survival.Conclusion: Our findings suggest that FCH-PET/CT may play a role in defining prognosis of patients receiving enzalutamide because baseline SUVmax proved to be an independent prognostic factor.